Knowledge, attitudes, practices and behaviors associated with female condoms in developing countries: a scoping review - Moore L; Beksinska M; Rumphs A; Festin M; Gollub EL (Dove Medical Press, 2015)
Lizzie Moore,1 Mags Beksinska,1,2 Alnecia Rumphs,3 Mario Festin,4 Erica L Gollub3 1MatCH Research (Maternal, Adolescent and Child Health Research), Department of Obstetrics and Gynaecology, University of the Witwatersrand, Westville, Durban, South Africa; 2Faculty of Epidemiology and Population Health, London School of Hygiene and Tropical Medicine, London, UK; 3Florida International University, Department of Epidemiology, Stempel College of Public Health and Social Work, Miami, FL, USA; 4World Health Organization, Special Program of Research, Development and Research Training in Human Reproduction, Department of Reproductive Health and Research, World Health Organization, Geneva, Switzerland Abstract: Women in developing countries are at high risk of HIV, sexually transmitted infections, and unplanned pregnancy. The female condom (FC) is an effective dual protective method regarded as a tool for woman's empowerment, yet supply and uptake are limited. Numerous individual, socioeconomic, and cultural factors influence uptake of new contraceptive methods. We reviewed studies of FC knowledge, attitudes, practices, and behaviors across developing countries, as well as available country-level survey data, in order to identify overarching trends and themes. High acceptability was documented in studies conducted in diverse settings among male and female FC users, with FCs frequently compared favorably to male condoms. Furthermore, FC introduction has been shown to increase the proportion of "protected" sex acts in study populations, by offering couples additional choice. However, available national survey data showed low uptake with no strong association with method awareness, as well as inconsistent patterns of use between countries. We identified a large number of method attributes and contextual factors influencing FC use/nonuse, most of which were perceived both positively and negatively by different groups and between settings. Male partner objection was the most pervasive factor preventing initial and continued use. Importantly, most problems could be overcome with practice and adequate support. These findings demonstrate the importance of accounting for contextual factors impacting demand in FC programming at a local level. Ongoing access to counseling for initial FC users and adopters is likely to play a critical role in successful introduction. Keywords: condoms, HIV prevention, contraception, female condom, developing countries, behavior